How norms can generate conflict - Fabian Winter; Heiko Rauhut; Dirk Helbing (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Norms play an important role in establishing social order. The current literature focuses on the emergence, maintenance and impact of norms with regard to coordination and cooperation. However, the issue of norm-related conflict deserves more attention. We develop a general theory of normative conflict by differentiating between two different kinds of conflict. The first results from distinct expectations of which means should be chosen to fulfil the norm, the second from distinct expectations of how strong the norm should restrain the self-interest. We demonstrate the empirical relevance of normative conflict in an experiment that applies the strategy method to the ultimatum game. Our data reveal normative conflict among different types of actors, in particular among egoistic, equity, equality and cherry picker types
Keywords: Z130; C91; D30; 330; Social norms; normative conflict; cooperation; ultimatum game; strategy method; equity; Soziale Norm; Sozialer Konflikt; Kooperation; Verhandlungstheorie; Test